Influence of product quality, price, and promotion on purchase decision of Philips Products - Firmansyah, Firmansyah (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2021)
The purpose of this study, among others, is to partially determine the effect of product quality on purchasing decisions for Philips products at PT. Sumber Peni Karya Pekanbaru, to partly assess the impact of price on buying decisions for Philips products at PT. Sumber Peni Karya Pekanbaru, to determine the effect of promotion partially on purchasing decisions at PT. Sumber Peni Karya Pekanbaru, and to assess the impact of product quality, price, and promotion simultaneously on purchasing decisions at PT. Source of Peni Karya. The population in this study amounted to 47 people, while the sample obtained was 47 samples. The data analysis technique used multiple linear regression analysis. The results of this study are that product quality affects purchasing decisions, and the price has a significant effect on purchasing decisions. The promotion does not affect purchasing decisions, and product quality, price, and advertising have a simultaneous or simultaneous impact on buying decisions.